International Teacher Identity Construction: A Story of An Afghan International Student - Lestari Budianto (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2022)
Foreign language plays important role in constructing a new identity for an international student. This paper explored the role of English for an international student studying in an Indonesian institute in constructing a new identity as an international teacher in Indonesia. This research used qualitative as the method and narrative inquiry became the research design. The participant of this research was an Afghan international student pursuing a master's degree in an Indonesian institute. The data were obtained through semi-structured interviews and documentation. The findings of this research showed that English skills were needed to show that the participant was an international teacher and English was beneficial for the participant in constructing a new identity as an international teacher in Indonesia. The participant had started learning English in his Junior High School and practiced using it intensively when the participant went abroad to continue his study for bachelor’s and master’s degrees. This research also revealed that having good speaking skills opened an opportunity for the participant to apply for a job as an English international teacher in Indonesia. Moreover, the speaking skills and international English teacher identity created a bridge for the participant to be a speaker for some events such as seminars and English-based events held by schools and institutes. This research was limited to a participant from a country and focused on teacher identity. It is suggested for future research to conduct similar research with more various participants from various countries and focus on another kind of identity construction.